PENGINTEGRASIAN KEUNGGULAN LOKAL PADA PEMBELAJARAN IPS MODEL INKUIRI DI KELAS VII C SMPN 1 MARABAHAN - Zainun Martha (JURNAL SOCIUS, 2013)
Low student motivation. The study aims to describe the students' motivation at gradeVII C SMPN 1 Marabahan,  on the subject of human life and the environment understanding and  the understanding of human social life through the integration of local advantages by model of inquiry.The research method used in the study of the class action is a method of qualitative analysis, which emphasizes on efforts to depictions of things that are associated with increased motivation through the integration of local excellence in the inquiry model of an integrated social studies. The  qualitative analysis of the researchers focused on extracting data according to the material so that it can be seen the problem and its solution on the activity of reflection. The research process began in September through December 2011, the number of samples of students are 36 in grade VII C.  The results showed that: (1) Motivation to learn at grade VII C SMPN 1 Marabahan in integrated social studies through the integration of local advantages be increased, (2) Motivation to learn at grade VII C  SMPN 1 Marabahan  for use in the inquiry learning model of the integrated social studies shows increased (3) Implementation of the Model inquiry can enhance students' motivation  at grade VIIC  SMPN 1 Marabahan. Researchers recommend that teachers should be social studies using the inquiry  model and integrating local adventages to a suitable material.Keywords: motivation, integration of local advantages, model inquiry, Social studies